Communication for end-of-life care planning among Korean patients with terminal cancer: A context-oriented model. Issue 1 (3rd July 2015) - Koh, Su Jin; Kim, Shinmi; Kim, Jinshil
ABSTRACT: Objective: In Korea, patients with terminal cancer are often caught out of the loop in end-of-life (EoL) care discussions. Healthcare professionals also have difficulty engaging in such communication in a variety of healthcare contexts. Therefore, the objective of our study was to develop a communication model for EoL care decision making compatible with the clinical environment in Korea. Methods: Using focus-group interview methodology, participants included eight doctors and five nurses who provide EoL care for terminal cancer patients in acute hospital settings or hospice care facilities in various provinces of Korea. Results: Five themes emerged regarding EoL care discussion, which included: (1) timing, (2) responsible professionals, (3) disclosure of bad news, (4) content areas of EoL care discussion, and (5) implementing strategies for EoL care discussions. These themes were based on development of a communication algorithm for EoL discussion among patients with terminal cancer. A structural communication step for delivery of a terminal prognosis was specified at the phase of disclosure of bad news: beginning with determination of a patient's decision-making capability, followed by a patient's perception of his/her condition, a patient's wish to know, family dynamics, and a patient's and/or family's readiness for EoL discussions. Significance of Results: The proposed context-oriented communication algorithm could provide a helpful guideline for EoL communication and, accordingly, facilitate meaningful improvements in EoL care in Korean clinical practice. The feasibility of this algorithm has not yet been determined, and its validation in a larger sample of patients with terminal cancers, using a quantitative research methodology, is a priority of research.